A study of celak form and its characteristics / Nurul Farida Harudin, Arba’iyah Ab. Aziz and Mohamad Kamal Abd. Aziz - Harudin, Nurul Farida; Ab. Aziz, Arba’iyah; Abd. Aziz, Mohamad Kamal (Faculty of Art and Design, 2023)
Celak (eyeliner), which is one of the personal ornaments, has been used since Ancient Egypt and is popular, especially among Arab and Asian communities. In spite of this, prior study has revealed that many younger generations are not familiar with or are uninterested in the meaning behind the design and meaning specifically depicted on the silver container of Celak. This study examines the characteristics of the Celak. In terms of research methodology, the researcher used two types of data collection, namely primary and secondary data. The primary data in this study are observations, while the secondary data include books, journals, articles, newspapers, and websites. As a result, it has become clear that Celak comes in a variety of designs and motifs. The shape of the Celak mostly looks like a tree with two leaves on top, round and globular shapes. The uniqueness of these personal ornaments such as Celak can be seen through their silversmithing and this study will benefit the younger generations in acknowledging the design and meaning of Celak. At the end of this study, the research outcome is anticipated to be used as a reference for other students and researchers.